Context Effects and the Manifestation of Grice’s Maxims in Wolio Proverbs: A Pragmatic Study: Context Effects and the Manifestation of Grice’s Maxims in Wolio Proverbs: A Pragmatic Study - Firman Alamsyah Mansyur (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2026)
This study aims to describe the influence of situational, social, and cultural contexts on the interpretation of Wolio proverbs and explain the manifestation of Grice's cooperative principle through the maxims of quantity, quality, relevance, and manner of use. This study uses a pragmatic approach with a qualitative descriptive method. Data were collected through literature review, in-depth interviews with native speakers, and observation of the use of proverbs in real communication. The analysis was conducted by interpreting the meaning of proverbs based on the surrounding context, then mapping the realization of Grice's maxims in the structure of the utterance and the strategy of using the proverb. The results of the study indicate that context has a direct and determining influence, as the meaning and function of proverbs can only be understood correctly when the speech situation, social relations, and cultural values are taken into account. In addition, Grice's principle of cooperation is reflected in the proverb as an effective, polite, and culturally normative communication strategy. These findings confirm the contribution of Wolio proverbs to the study of pragmatics and cultural linguistics and have the potential to be used as educational material to strengthen cultural literacy and communication values.